Study of the initial material and its use in winter durum wheat breeding for resistance to the Rostov population of the smut pathogen - T. G. Derova; N. V. Shishkin; N. E. Samofalova (Зерновое хозяйство России)
The current paper has presented the study results of the resistance of winter durum wheat varieties to the causative agent of smut under infectious background conditions. The purpose of the study was to identify new sources of smut resistance of winter durum wheat under conditions of artificial inoculation and their use in breeding programs. In the period from 2010–2022 there were studied annually more than 100 varieties and samples. According to the results of 2010, practically resistant varieties of Competitive (CVT) and Interstation Variety Testing (IVT) amounted to 1.4 and 6.7 % of those studied. The bulk has been represented by moderately susceptible and susceptible varieties. By 2015, among the selection samples, practically resistant and slightly susceptible ones amounted to 12.5 and 15.0 %. In 2022, the number of practically resistant ones increased to 26.9%, and weakly susceptible ones raised to 27.9 %. There have been identified the sources of resistance to the Rostov population of the smut pathogen. After introducing into the breeding process such sources of resistance as ‘Delta Odesskaya’, ‘Perlina Odesskaya’, ‘Dnepryana’, ‘Kermen’, etc., there have been developed the varieties ‘Agat Donskoy’, ‘Lazurit’, ‘Kremona’, ‘Oniks’ with practical resistance to the pathogen at the ARC “Donskoy”. Subsequently, when updating the initial material, there have been studied the new varieties of MSI and there have been identified such smut-resistant varieties as ‘Poseidon’, ‘Pributkova’, ‘Andromeda’, ‘Zhivitsa’, ‘Prikumskaya 142’, ‘Kharkovskaya 32’, etc. Using several of them in hybridization, because of many years of selection, there have been developed new winter durum wheat varieties with practical resistance, weak and medium susceptibility to smut, such as ‘Yubilyarka’, ‘Zoloto Dona’, ‘Lakomka’, ‘Dinas’, ‘Solntsedar’, ‘Karotinka’, ‘Grafit’, etc. Among the CVT samples there have been also identified such lines with smut resistance as ‘1273/19’, ‘335/20’, ‘893/20’, ‘1383/20’, etc. The identified sources and the developed pathogen-resistant varieties are recommended for use in breeding programs for winter durum wheat.